QuickDraw: Improving Drawing Experience for Geometric Diagrams - Cheema, Salman; Gulwani, Sumit; Jr., Joseph J. LaViola (CHI'12, May 5-10, 2012, Austin, Texas, USA, 2012)
We present QuickDraw, a prototype sketch-based drawing tool, that facilitates drawing of precise geometry diagrams that are often drawn by students and academics in several scientific disciplines. Quickdraw can recognize sketched diagrams containing components such as line segments and circles, infer geometric constraints relating recognized components, and use this information to beautify the sketched diagram. Beautification is based on a novel algorithm that iteratively computes various sub-components of the components using an extensible set of deductive rules. We conducted a user study comparing QuickDraw with four state-of-the-art diagramming tools: Microsoft PowerPoint, Cabri II Plus, Geometry Expressions and Geometer’s SketchPad. Our study demonstrates a strong interest among participants for the use of sketch-based software for drawing geometric diagrams. We also found that QuickDraw enables users to draw precise diagrams faster than the majority of existing tools in some cases, while having them make fewer corrections.